Mathematics from creating the pyramids to exploring infinity - Rooney, Anne (How the world works, 2017)
In order to understand the universe you must know the language in which it is written. And that language is mathematics. People have always sought order in the apparent chaos of the universe. Mathematics has been our most valuable tool in that search, uncovering the patterns and rules which govern our world and beyond. This book traces humankind's greatest achievements, plotting a journey through the mathematical intellects of the last 4,000 years to where we stand today